Effect of Trastuzumab on Cardiac Function Does Not Increase over Time - Helwick, Caroline (MD Conference Express, 2007)
This article discusses the effect of trastuzumab on cardiac function, the final results from the phase 3 Intergroup Trial E1199, novel regimens for the treatment of triple-negative breast cancer tumors, and a comparison of magnetic resonance imaging versus mammography in detecting ductal carcinoma in situ.